MonTh: A Tool for Automated Monitoring of Threats - Urbano, Arthur; Silva, Douglas; Mesquita, Maria; Costa, Yago Melo; Cirino, Mariana; Gomes, Rafael Lopes (Companion Proceedings of the Latin-American Symposium on Dependable and Secure Computing (LADC); 2023: Companion Proceedings of the 12th Latin-American Symposium on Dependable Computing, 2023)
The growing sophistication of cyber threats demands advanced solutions to protect data integrity and confidentiality. One approach to dealing with this scenario is Threat Intelligence, which is crucial in enabling companies and institutions to gather data about potential threats and address security incidents based on that information. Within this context, this work presents the MonTh tool for data collection from VirusTotal, AbuseIPDB, Shodan, IBM X-Force, and AlienVault databases. This tool empowers companies/institutions to update automatically on new threats emerging through valuable indicators concerning suspicious IPs and domains.